Mitigasi Bencana Banjir pada Kawasan Permukiman di Kabupaten Bengkalis Provinsi Riau - Syahputra, Roji; U, Iswandi (Lembaga Yasin AlSys, 2025)
This study aims to: (1) determine the level of flood vulnerability and the affected areas in Bengkalis Regency, Riau Province; and (2) analyze both the current and necessary flood disaster mitigation efforts in the region. A quantitative descriptive method was employed, utilizing a Change Detection approach to identify flood-inundated areas, and Interpretative Structural Modeling (ISM) as a decision-support tool for mitigation planning. The results indicate that flood vulnerability is primarily influenced by low slope gradients (0–8%), which facilitate rainwater accumulation, and high annual rainfall (>3000 mm), which accelerates surface runoff. The extent of affected areas includes 2,792.19 hectares for biennial floods, 10,995.18 hectares for five-year floods, and 67,825.93 hectares for floods occurring every ten to twenty years. Biennial floods impact 248 houses in villages such as Sekodi, Kelemantan, and Teluk Pambang. Five-year floods affect 681 houses in villages including Ketam Putih, Batu Panjang, and Muara Basung. Meanwhile, ten- to twenty-year floods affect 3,473 houses in areas like Sungai Alam, Pematang Duku, and Petani. ISM analysis reveals that the top-priority mitigation strategy lies at level 5, specifically element A6, which concerns the disaster planning conducted by the Regional Disaster Management Agency (BPBD). These findings underscore the urgency of structured and adaptive disaster planning to minimize flood risks and impacts in Bengkalis Regency.